Role Playing Simulation Learning Method in Disaster-Prone Areas: Is It Effective in Improving Knowledge and Preparedness for Disasters? - Khusna, Nur Isroatul; Mulabbi, Andrew; Maunah, Binti; Putranto, Anggoro; Zahroh, Lulul 'Atirotu (International Journal of Social Learning (IJSL), 2025)
Indonesia is a disaster-prone country, especially in terms of geological disasters. Applying disaster education through simulation methods is expected to give the community the right knowledge and attitude toward disaster response. This study aimed to determine and analyze the knowledge and attitudes of students in higher education in responding to geological disasters through simulation learning methods. The population in this study was students of the Social Sciences Education Study Program from five Islamic universities in East Java, Indonesia, and the sample was 378 students. The method used was quantitative with univariate and bivariate data analysis. The study results from the analysis stated a significant difference between the knowledge and preparedness of geological disasters in students in the control group and the experimental group, with a P value of 0.0001. Thus, the knowledge and disaster preparedness level in students who received simulation learning was higher than in students who did not receive learning with the simulation learning model. This study implies that the simulation learning model can be used as a reference in implementing disaster education, especially in disaster-prone areas.